Strategies used by midwives to enhance knowledge and skill development in midwifery students: an appreciative inquiry study - Fiona Arundell; Athena Sheehan; Kath Peters (BMC, 2024)
Abstract Background Midwifery practice experience for midwifery students is an important component of education to enhance knowledge and skill development. Practicing midwives provide student support in the clinical setting, there is minimal literature relating to strategies midwives use to support students. Objective To explore midwifery student experiences of the strategies used by midwives to facilitate knowledge and skill development in the clinical practice setting. Methods Qualitative approach based on Appreciative Inquiry. The setting is one University in Australia. Participants, thirteen Graduate Diploma in Midwifery students. Individual interviews followed by thematic analysis. Results Data analysis identified six themes, Willingness to share knowledge and develop skills; The positive use of questioning; Moderating support; Teaching through the woman; Learning through problematisation and Providing constructive affirmation. Conclusions Midwives incorporated varied strategies to support student development in the clinical setting. For an equitable clinical experience, all midwives need support to develop skills and confidence in facilitating student learning.